Applying a pelvic corrective force induces forced use of the paretic leg and improves paretic leg EMG activities of individuals post-stroke during treadmill walking. Issue 10 (October 2017) - Hsu, Chao-Jung; Kim, Janis; Tang, Rongnian; Roth, Elliot J.; Rymer, William Z.; Wu, Ming
Highlights: A mediolateral assistance force was applied to the pelvis toward the paretic side during walking. Applying pelvic assistance may enhance paretic leg muscle activity and improve walking pattern. Forceful weight shift to the paretic side could induce forced used of the paretic leg. Abstract: Objective: To determine whether applying a mediolateral corrective force to the pelvis during treadmill walking would enhance muscle activity of the paretic leg and improve gait symmetry in individuals with post-stroke hemiparesis. Methods: Fifteen subjects with post-stroke hemiparesis participated in this study. A customized cable-driven robotic system based over a treadmill generated a mediolateral corrective force to the pelvis toward the paretic side during early stance phase. Three different amounts of corrective force were applied. Electromyographic (EMG) activity of the paretic leg, spatiotemporal gait parameters and pelvis lateral displacement were collected. Results: Significant increases in integrated EMG of hip abductor, medial hamstrings, soleus, rectus femoris, vastus medialis and tibialis anterior were observed when pelvic corrective force was applied, with pelvic corrective force at 9% of body weight inducing greater muscle activity than 3% or 6% of body weight. Pelvis lateral displacement was more symmetric with pelvic corrective force at 9% of body weight. Conclusions: Applying a mediolateral pelvic corrective force toward the paretic side may enhance muscle activity of the paretic leg and improve pelvis displacement symmetry in individuals post-stroke. Significance: Forceful weight shift to the paretic side could potentially force additional use of the paretic leg and improve the walking pattern.